Caracterización del estado mental de migrantes venezolanos en condición de desplazamiento (2023)
The purpose of this degree work was to characterize the mental status of a sample of the Venezuelan population in a condition of forced displacement that resides in the Villa Caracas neighborhood, in the city of Barranquilla, Colombia. Method: For this, a quantitative research of an empirical analytical paradigm was carried out, with a descriptive scope, with a non-experimental, cross-sectional design, together with a non-probabilistic-incidental documentary. The population and sample consisted of 102 Venezuelan immigrant subjects. For the collection of information, 4 instruments were applied: Memory, Fluency and Orientation (MEFO), Generalized Anxiety Scale (GAD-7), Depression Questionnaire (PHQ-9) and Clinical Classification of Dementia (CDR). Results: It was determined that the population stands out for being elderly, with a low educational level, lack of monetary income, low academic level and high levels of unemployment, in addition to presenting moderate nxiety and depression, together with a cognitive deficit and absence of dementia